PERFORMANCE IMPROVEMENT THROUGH STRENGTHENING ENTREPRENEURSHIP, INNOVATIVENESS, AND E-COMMERCE IMPLEMENTATIONS OF MSMEs TO OPERATIONAL MANAGER IN SERANG, BANTEN PROVINCE - Ahmad Mukhlis; Anoesyirwan Moeins; Widodo Sunaryo (International Journal of Economy, Education and Entrepreneurship, 2022)
Indonesia is one of the countries supported by the MSME sector. The significance of factors that encourage mitigation and economic recovery in Serang, Banten, by increasing the performance of MSMEs has been the subject of some studies, and these studies all reach the same conclusion. This research aims to identify methods and approaches to performance enhancement that are suitable for small groups of MSME Operations Managers in Serang City. Research must carry out on the factors that have an impact on performance. These factors include entrepreneurship, innovation, and e-commerce. Methods from multiple research traditions combine to form this study (mixed methods). This study used a multistage random sampling technique to collect data from 240 MSME business owners from the small business group in the city of Serangby. The findings of quantitative research indicate that there is a significant direct effect between entrepreneurship and performance; between innovation and performance; between e-commerce and performance; between entrepreneurship and e-commerce; between creation to e-commerce; and that there is a significant indirect effect between entrepreneurship and performance through e-commerce; between innovation and performance through e-commerce. The findings of the qualitative research lend credence to the results of the quantitative study, which found that the low indicators of the effectiveness of education and training in the dimension of work effectiveness need to be improved to strengthen the performance of the MSME Operational Managers of small business groups in the city of Serang. According to the study's findings, the performance of MSME Operational Managers for small business groups can improve by boosting entrepreneurialism and innovation through implementing e-commerce. It is one of the recommendations made by the researchers